CCL2/CCR2 Chemokine System in Embryonic Hypothalamus: Involvement in Sexually Dimorphic Stimulatory Effects of Prenatal Ethanol Exposure on Peptide-Expressing Neurons. (1st January 2020) - Chang, Guo-Qing; Karatayev, Olga; Devi Sai Sri Kavya, Boorgu; Leibowitz, Sarah F.
Highlights: Prenatal ethanol exposure stimulates CCL2, MCH and their colocalization in LH of the embryo and neonate. These effects of prenatal ethanol exposure are sexually dimorphic, stronger in female than male embryos. Endogenous CCL2 and CCR2 receptors are required for prenatal ethanol's stimulatory effect on MCH neurons. These effects in the embryo are long lasting, similar to those described in adolescent offspring that affect behavior. Abstract: Maternal consumption of ethanol during pregnancy is known to increase the offspring's risk for developing alcohol use disorders and associated behavioral disturbances. Studies in adolescent and adult animals suggest the involvement of neuroimmune and neurochemical systems in the brain that control these behaviors. To understand the origin of these effects during early developmental stages, we examined in the embryo and neonate the effects of maternal intraoral administration of ethanol (2 g/kg/day) from embryonic day 10 (E10) to E15 on the inflammatory chemokine C-C motif ligand 2 (CCL2) and its receptor CCR2 in a specific, dense population of neurons in the lateral hypothalamus (LH), where they are closely related to an orexigenic neuropeptide, melanin-concentrating hormone (MCH), known to promote ethanol consumption and related behaviors. We found that prenatal ethanol exposure increases the expression and density of CCL2 and CCR2 cells along with MCH neurons in the LH and the colocalization of CCL2 with MCH. We also discovered that these effects are sexually dimorphic, consistently stronger in female embryos, and are blocked by maternal administration of a CCL2 antibody (1 and 5 µg/day, i.p., E10-E15) that neutralizes endogenous CCL2 and of a CCR2 antagonist INCB3344 (1 mg/day, i.p., E10-E15) that blocks CCL2′s main receptor. These results, which in the embryo anatomically and functionally link the CCL2/CCR2 system to MCH neurons in the LH, suggest an important role for this neuroimmune system in mediating ethanol's sexually dimorphic, stimulatory effect on MCH neurons that may promote higher level of alcohol consumption described in females.